2014
DOI: 10.1016/j.egypro.2014.07.229
|View full text |Cite
|
Sign up to set email alerts
|

Wave Influenced Wind and the Effect on Offshore Wind Turbine Performance

Abstract: In this paper the effect of wave influenced wind on offshore wind turbines is studied numerically.The wave is seen as a dynamical roughness that influences the wind flow and hence the wind turbine performance. An actuator line representation of the NREL's 5 MW offshore baseline wind turbine is placed in a simulation domain with a moving mesh that resolves the ocean waves. These wave influenced wind turbine simulations, WIWiTS, show that the wave will influence the wind field at the turbine rotor height. Both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…1. As shown by the aforementioned studies [18,19,20], aligned wind-wave directions result in higher velocities and thus in higher power productions compared to no waves. The opposite is probably true for opposed wind-wave directions, since they have a higher roughness length causing the wind speed and thus the wind turbine power production to decrease [21].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…1. As shown by the aforementioned studies [18,19,20], aligned wind-wave directions result in higher velocities and thus in higher power productions compared to no waves. The opposite is probably true for opposed wind-wave directions, since they have a higher roughness length causing the wind speed and thus the wind turbine power production to decrease [21].…”
Section: Introductionmentioning
confidence: 93%
“…were not addressed in these studies. Simultaneously, [20] performed unsteady Reynolds-Average Navier-Stokes (URANS) simulations and found indications of an effect of the wind-wave alignment on the power production of wind farms, even though the simulations did not numerically converge due to an incomplete grid independence.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a hybrid numerical model (LES coupled with high-order spectral-wave simulations), Xiao et al [52] found that swell introduces a periodic oscillation in the extracted WPD from a fixed turbine, and it has much larger influences on the floating turbine case. The produced power and the tangential forces on the rotor blades can be altered by ocean waves [16]. Thus, the surface wave impact on the wind profile needs to be investigated in a further study when mapping the WPD over coastal areas.…”
Section: Sea-state-dependent Stressmentioning
confidence: 99%
“…On the low wind and swell conditions, the wind simulation is improved when sea-state-dependent wind stress parameterization is implemented into an atmosphere-wave-coupled system [12]. Based on computational fluid dynamics (CFD) simulations with a moving mesh that resolves the ocean waves, Kalvig et al [16] found that the wind field at the turbine rotor height varies with different wave states. The atmospheric stability is another important factor when estimating the offshore wind power [17], which is primarily determined by the air-sea temperature difference.…”
Section: Introductionmentioning
confidence: 99%
“…Each grid cell moves now up and down, reaching its maximum elevation at different time increments according to a sinusoidal function, and the movement looks like a wave propagating -much like the surface particles in a real ocean wave. In [6][7][8] a more detailed description of the model is available.…”
Section: Wave Generation Actuator Line Model and Fastmentioning
confidence: 99%